Acompanhamento do controle de qualidade de diversos produtos saneantes - Moreira, Melissa Caludino Dantas (Universidade Federal Rural do Semi-Árido, 2019)
Household sanitizers are substances or preparations intended for household sanitation, disinfection or disinfestation, in collective or public environments and in the treatment of water. They can be classified as to their purpose, degree of risk, sale and employment. Bleach, fabric softener, detergents and disinfectants are the main types of sanitizers. ANVISA is the organ of the Ministry of Health responsible for the regulation and inspection of the sanitizing trade, it requires companies to develop products that are safe and with strict quality control. Sabão Juá Industry verifies the quality of raw materials and their products through physical-chemical analyzes such as pH, viscosity, density, chlorine content, foam index, acidity index free, moisture content. Through the control chart it is possible to analyse the variability of a productive process, thus informing if the process is under statistical control.
Monografia
Keywords: Saneantes domissanitários; Controle de qualidade; ANVISA; Análises físico-químicas; Household sanitizers; Quality control; ANVISA; Physicochemical analysis; ENGENHARIAS::ENGENHARIA QUIMICA